PENGAMBILAN KEPUTUSAN MENGENAI ANGGARAN PENDAPATAN DAN BELANJA DESA DI DESA RASAU JAYA 1 - Bambang Suko Winarno E.21108130 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The research initial problem in the rural of Rasau Jaya 1 that occurs is the issue of rural irrigation, construction of roads and markets rural. This article is intended to provide an understanding of the decision making process by Rural Discussion Forum Board in the income and Budget rural. The issues raised in the rural of Rasau Jaya 1 which is still less absorption aspirations of the people in the rural that physical development is not in accordance with the aspirations of the people submit through musrenbangdes. In this study the authors used qualitative methods to answer the research results and also conduct interviews from various sources in accordance with the predetermined subject, such as : Chairman BPD Rural of  Rasau Jaya 1 , Head Rural  , Rural and Community Leaders Rasau Jaya 1 in order to obtain data for the author.The results of this study , the authors found the lack Village Consultative Body in facilitating the aspirations of rural communities to develop rules mainly Budget Shopping Village , resulting in the implementation of the physical construction of the village is not in accordance with what the public wants. Recommendations from the research that has been conducted by the author , namely the need for regular meetings held by the Consultative Board to the village and village community to the presence of harmony to the physical development of the village in accordance with the aspirations which has been submitted , as well as in decision-making should be done by consensus to consensus and is not based on personal and group interests . Keyword : Decision Making, Rural Regulation, Rural Physical Development